The Influence of Free Social Interaction and Peer Pressure on Adolescent Behavior in Helvetia Village, Labuhan Deli District - Anggun Syahfitri; Minna Bella; Naila Nafisah Zulfa; Riwati Amelia; Sani Susanti (Parpudi: Journal Of Community and Adult Learning, 2025)
Adolescence is a critical developmental stage characterized by heightened vulnerability to social influence, particularly peer pressure and unregulated social interaction. This study examines the influence of free social interaction and peer pressure on adolescent behavior in Helvetia Village, Labuhan Deli District. Using a qualitative descriptive approach, data were collected through in-depth interviews, non-participant observation, and documentation involving adolescents, parents, and community representatives. The findings indicate that adolescents are increasingly exposed to unregulated social environments, manifested in late-night socializing, experimentation with cigarettes and alcohol, school absenteeism, and excessive engagement with social media trends. Peer pressure emerges as a dominant factor shaping these behaviors through mechanisms of persuasion, conformity, and fear of social exclusion. The study further reveals that weak parental supervision and limited community control exacerbate adolescents’ susceptibility to negative peer influence. As a follow-up intervention, a structured counseling program was implemented to enhance adolescents’ awareness of social risks and develop assertive skills in resisting negative peer pressure. The results underscore the importance of integrated efforts involving families, schools, and communities in fostering healthy adolescent development and preventing social deviance.